REPRODUCTIVE HEALTH MIDWIFERY CARE IN NY “K” WITH A FOCUS ON SOY MILK INTERVENSION TO REDUCE INSOMNIA IN PREMENOPAUSAL WOMEN AT INDEPENDENT PRACTICE MIDWIFE Bd.Tri W - Cindy Putri Octivia; Rizki Sahara; Sri Untari (The Shine Cahaya Dunia Kebidanan, 2023)
Background; Based on the 2012 Indonesian Health Demographic Survey (IDHS) regarding menopause, there were 4.3 million Indonesians totaling 240-250 million in 2012. In this category of women (over 46-49 years old) 18% of Indonesian women have experienced menopause with all the consequences and impacts that accompany it (Depkes RI, 2012). Based on the results of a preliminary study conducted by the author in May 2022 in Boloh Village, RT 01/03 RW of 10 premenopausal women aged 40-50 years, 8 out of 10 people experience premenopausal symptoms, especially insomnia. Method; The research design that the researcher uses is a case study research design. This type of descriptive case study research uses participatory observation method. The subjects in this study were premenopausal women. Result; The results showed that Ny.K's diagnosis was sleep disturbance and a little anxiety about the condition she was experiencing. Evaluation of the implementation of soy milk in the case of Ny. K with insomnia there is a reduction in the insomnia scale score 16 to the insomnia scale score 14 (moderate). Conclusion; The problem of insomnia and a little anxiety about the condition he was experiencing had been resolved.